An Analysis of Sociogenesis Motive of Main Character in “Unbroken” Movie - Juwita Boneka Sinaga (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2017)
This research entitled “An Analysis of Sociogenesis Motive of Main Character in ‘Unbroken’ movie. It discussed the socio genesis  of the main character in the movie "UNBROKEN", Unbroken movie which released in 2014 American biographical thriller film in sydney, Australia. This research analyzed the sociogenesis motives of Louis that reflected in “Unbroken” movie. This research applied a qualitative research method. Data collection procedures was got by watching the movie repeatedly, took important data, arranged the data, looked for supporting data and arranged the data sistematically. The method which was used by the writers in analyzing the conflict of the main character in this movie was a descriptive qualitative method.  . Data analysis procedures was analyzed by using the  quotation of the film. Primary data source was Unbroken movie. While secondary data sources were collected from many sources such as the articles, script of movie, biography of the author,  journal from internet, and books related to this research as references to support the data found. Based on the result of analysis, the answer to question was as follows. Louis’s sociogenesis motives was sociogenesis motive with the natural condition of life (drowning, huge waves, strong wind, scorching sun, shortage of food), sociogenesis motives with other species (shark’s attack) and sociogenesis motives with members of one’s own species (contumely from watanabe, the bird). It was concluded that Louis is a man that had incredible sociogenesis motive to survive with the difficult situation. In this research, the writer described how the personal conflict of the main character in the movie "Unbroken" was.